Scattering of elastic waves by a general anisotropic basin. Part 2 a 3D model. - Dravinski, Marijan
Scattering of plane harmonic waves by a three dimensional basin of arbitrary shape embedded within elastic half space is investigated by using an indirect boundary integral equation approach. The materials of the basin and the half space are assumed to be the most general anisotropic, homogeneous, linearly elastic solids without any material symmetry (i.e. triclinic). The unknown scattered waves are expressed in terms of three dimensional triclinic time harmonic full space Green's functions. The results have been tested by comparing the surface response of semi spherical isotrophic and transversely isotropic basins for which the numerical solutions are available. Surface displacements are presented for a semicircular basin subjected to a vertical incident plane harmonic pseudo-P-, SV- or SH wave. These results are compared with the motion obtained for the corresponding equivalent isotrophic models. The results show that presence of the basin may cause significant amplification of ground motion when compared to the free field displacements. The peak amplitude of the predominant component of surface motion is smaller for the anisotropic basin than for the corresponding isotropic one. Anisotropic response may be assymetric even for anisotropic basin than for the corresponding isotropic one. Anisotropic response may be asymmetric even for symmetric geometry and incidence. Anisotropic surface displacement generally includes all three components of motion which may not be the case for the isotropic results. Furthermore, anisotropic response strongly depends upon the nature of the incident wave, degree of material anisotropy and the azimuthal orientation of the observation station.
Keywords: Three dimensional anisotropic basin; Site response